A Cancellation-Free Symbolic Sensitivity Technique Based on Network Determinant Expansion. (21st September 2015) - Filaretov, Vladimir; Gorshkov, Konstantin; Kurganov, Sergey
Abstract : The generalization of Bode's sensitivity analysis technique for all types of the transfer functions and circuit elements is presented in the paper. The proposed formulae for first- and second-order symbolic sensitivity calculation provide the compact size of obtained expression and have the advantages of cancellation-free sum-of-product terms and matrix-free computation. This is achieved by means of the concept of high order summative cofactors and the generalized parameter extraction method. The proposed technique is implemented in symbolic circuit analysis program Cirsym. Illustrative example on symbolic sensitivity circuit analysis and comparison of the presented technique with the transimpedance method and the method based on the modified Coates flow-graph are given.